Management of Dental Health Problem of Diabetic Patients Attending in Selected Private Dental Clinic in Dhaka City (Bangladesh Journal of Dental Research & Education, 2015)
Aim: The rising cases of dental problems among diabetic patients have raised health concerns among dentists worldwide. The oral complications of prime concern are gum disease, dental caries, dry mouth, oral soft tissue damage, and pain in the face and mouth. This descriptive type of cross sectional study was conducted among the diabetic patients for their management of dental problems attending in selected dental clinic in Dhaka city from January to June 2012. 44% of the patients were in between 41to 50 years age group.Methods:  Data were collected with a pretested semi structured questionnaire and check list was filled in after oral examination.Results: Among the patients 84% were Muslims and 16%. were Hindu. All the patients were married. 58% of the patients had monthly income TK. 25000-40000. Among the patients, 48% had (4-5) family members. Type of family was single for 82% of the patients. Main food was rice for 78% of the patients. 50% of the patients had habit of tobacco use. Tobacco smokers were 88%. Among the patients, calculus and gingivitis was in grade I for 54% and the condition of periodontitis was in grade I for 46%. The condition of oral thrush was in 0 grade for 66% of the patients. Most of the patients 1 tooth was affected by dental caries. There was no dry mouth in 80% of the patients, whereas no burning mouth syndrome was in 82% of the patients; 64% of the respondents visited dentists. The reason for visiting dentists, most of them visited for sensitivity. All the patients brushed teeth everyday. 66% of the patients brushed teeth once a day. Among the patients 66% cleaned teeth before breakfast and 52% took 3-4 minutes. Among the patients, 90% used tooth brush and 88% used tooth paste for cleaning the teeth. 84% of them did not floss and the rest 62.5% flossed teeth once a day, 62% got information about type of diabetes, among them 62.5% informed about non insulin dependent type of diabetes. Among the patients, 60% got information about usual oral hygiene, 75.9% got information about usual oral hygiene from doctors.Conclusion: Proper patient management requires close interaction between the dentist and the physician. Working with diabetic patients can be challenging and rewarding when open communications are established and thorough patient education is attained.Bangladesh Journal of Dental Research and Education Vol.5(2) 2015: 55-58